Pengembangan Buku Ajar berbasis pemecahan masalah untuk meningkatkan pemahaman konsep pada Mata Kuliah Ekologi Tumbuhan - Ilma, Silfia; Wijarini, Fitri (Biosfer: Jurnal Pendidikan Biologi, 2025)
Cognitive learning outcomes (CLO) are the most important part of learning. CLO the basis of students' understanding for further learning. CLO play an important role in students' readiness to face the real world. Therefore, CLO needs to be facilitated in learning. CLO is related to the problem-solving process. This study aims to produce a problem-solving-based textbook to improve conceptual understanding in the Plant Ecology course. This research and development follow the 4D model consisting of define, design, develop, and disseminate. The instruments used in this study were questionnaires, validation sheets, and problem-solving-based test instruments in the form of essay questions. Data collection techniques used were observation, questionnaires, and tests. To determine the feasibility of problem-solving-based test instruments, the data analyzed were the results of validation by material experts and media experts. To determine the practicality of problem-solving-based tests, the data analyzed were the results of lecturer validation and student responses. The result of problem-solving-based textbook that has been compiled has met the validity criteria and practicality. In addition, problem-solving-based textbooks have an effect on CLO. Therefore, problem-solving-based textbooks are highly recommended in improving students' CLO. This means that there is an influence of problem-solving-based textbooks on CLO in the Plant Ecology course. Therefore, problem-solving based textbooks are highly recommended in improving students' CLO.